Identification of three kinds of Plumeria flowers by DNA barcoding and HPLC specific chromatogram - Leilei Zhao; Xiaoxue Yu; Jie Shen; Xinjun Xu (Elsevier, 2018)
DNA barcoding and HPLC specific chromatogram were used to identify three kinds of Plumeria flowers respectively. DNAs extracted from the three Plumeria species were amplified by PCR with universal primers, and the psbA-trnH region was selected. All the amplified products were sequenced and the results were analyzed by MEGA 5.0. Chemometric methods including principal components analysis and hierarchical clustering analysis were conducted on the SAS 9.0 software to demonstrate the variability among samples. In conclusion, the psbA-trnH of all samples were successfully amplified from total DNA and sequenced. These three varieties of Plumeria can be differentiated by the psbA-trnH region and clustered into three groups respectively through building neighbor joining tree, which conformed to their germplasm origins. However, it was hard to distinguish them by HPLC specific chromatograms combined with chemometrics analysis. These indicated that DNA barcoding was a promising and reliable tool for the identification of three kinds of Plumeria flowers compared to HPLC specific chromatogram generally used. It could be treated as a powerful complementary method for traditional authentication, especially for those varieties which are difficult to be identified by conventional chromatography. Keywords: Plumeria, DNA barcoding, HPLC specific chromatogram, Chemometrics analysis, Identification